1999
DOI: 10.1038/sj.leu.2401388
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by bestatin (ubenimex) in human leukemic cell lines

Abstract: We investigated the growth inhibitory activity of bestatin, an inhibitor of aminopeptidase N (CD13), on six human leukemic cell lines. Proliferation of all the cell lines except KG1 was inhibited by bestatin. P39/TSU, HL60 and U937 were highly sensitive, with 50% growth inhibitory concentrations (IC 50 ) close to the maximum serum concentration when bestatin was orally administered at 30 mg in clinical application. All cell lines except for K562 highly expressed CD13, but a clear correlation between the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 25 publications
(31 reference statements)
4
62
1
Order By: Relevance
“…AP inhibitors, such as actinonin and bestatin, have been reported to have anti-tumor effects through augmentation of the host immune system (21)(22)(23)(24)(25). More relevant to the present study, bestatin has been shown to induce apoptosis through inhibition of cell surface APN (15,26) and increase apoptosis in human leukemic cell lines by enhancing processing of caspase-3 in the presence of death-inducing ligands such as TNF␣ and CH11 (anti-Fas mAb) (27).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…AP inhibitors, such as actinonin and bestatin, have been reported to have anti-tumor effects through augmentation of the host immune system (21)(22)(23)(24)(25). More relevant to the present study, bestatin has been shown to induce apoptosis through inhibition of cell surface APN (15,26) and increase apoptosis in human leukemic cell lines by enhancing processing of caspase-3 in the presence of death-inducing ligands such as TNF␣ and CH11 (anti-Fas mAb) (27).…”
mentioning
confidence: 68%
“…One of the most widely studied AP is the 967-amino acid protein termed aminopeptidase N (APN). This peptidase is identical to the cell surface antigen CD13 (14) and displays activity toward an array of substrates, including the enkephalins, bradykinin, bacterial derived chemotactic peptides, tachykinins, and the cytokines granulocyte colony-stimulating factor, interferon-␥, IL-1␤, IL-2, IL-6, and IL-8 (15,16). Moreover, CD13 is involved in cell surface antigen processing through the "trimming" of HLA class II-or class I-bound peptides on antigenpresenting cells (17)(18)(19).…”
mentioning
confidence: 99%
“…That the target is most likely to be one or more members of the aminopeptidase class of metalloenzyme is indicated by the findings that (a) all active antiproliferative agents related to CHR-2797 were aminopeptidase inhibitors and (b) tumor cells that were sensitive to CHR-2797 were also sensitive to high concentrations of bestatin, a well-established, structurally distinct, aminopeptidase inhibitor (9). This agent is also thought to act within the cell: (a) intracellularly hydrolysable bestatin esters are more potent antiproliferative agents than bestatin itself (27) 5 and (b) agents that inhibit the extrusion of bestatin from the cell can enhance its antiproliferative potency (28). Extensive studies in sensitive leukemic cells using small interfering RNA (siRNA) reagents targeting individual intracellular aminopeptidases have failed to provide convincing evidence that any single enzyme is responsible for the effects of CHR-2797.…”
Section: Discussionmentioning
confidence: 99%
“…Bestatin, an inhibitor of aminopeptidase N, is reported to induce apoptosis of leukemia cells by enhancement of caspase-3, 16 to enhance cytotoxic activity of lymphocytes, 17 and to activate monocytes. 18 In the setting of BMT, administration of bestatin after transplantation promoted an increase of NK cells, B cells and CD4/CD8 ratio, 19 and decreased the rate of leukemia relapse via a GVL effect.…”
Section: Discussionmentioning
confidence: 99%